2021
DOI: 10.1155/2021/5542485
|View full text |Cite
|
Sign up to set email alerts
|

PAR2 Promoter Hypomethylation Regulates PAR2 Gene Expression and Promotes Lung Adenocarcinoma Cell Progression

Abstract: Objective. Protease-activated receptor-2 (PAR2) also known as F2RL1 is a G protein-coupled receptor that intimately correlates with cancer occurrence. DNA methylation turns out a vital mechanism regulating gene expression, while PAR2 promoter methylation is proven to be involved in cancer development. Hence, this study attempted to clarify the molecular mechanism by which PAR2 mediates lung adenocarcinoma (LUAD) progression, via identifying the effect of PAR2 promoter methylation on LUAD cell progression. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Moreover, the results of external validation based on five GEO datasets and prognostic meta-analysis all confirmed the relatively better robustness of the prognostic signature compared to previous studies (9,37). F2RL1, also known as protease-activated receptor 2 (PAR2), has been reported to be associated with the occurrence and development of lung adenocarcinoma (44) and intestinal tumors (45,46). A recent study revealed that hypomethylation of the F2RL1 promoter could upregulate its expression and promote the proliferation, migration, and invasion of LUAD cells (44).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Moreover, the results of external validation based on five GEO datasets and prognostic meta-analysis all confirmed the relatively better robustness of the prognostic signature compared to previous studies (9,37). F2RL1, also known as protease-activated receptor 2 (PAR2), has been reported to be associated with the occurrence and development of lung adenocarcinoma (44) and intestinal tumors (45,46). A recent study revealed that hypomethylation of the F2RL1 promoter could upregulate its expression and promote the proliferation, migration, and invasion of LUAD cells (44).…”
Section: Discussionsupporting
confidence: 66%
“…F2RL1 , also known as protease-activated receptor 2 ( PAR2 ), has been reported to be associated with the occurrence and development of lung adenocarcinoma ( 44 ) and intestinal tumors ( 45 , 46 ). A recent study revealed that hypomethylation of the F2RL1 promoter could upregulate its expression and promote the proliferation, migration, and invasion of LUAD cells ( 44 ). The ADRB2 gene encodes the beta2-adrenergic receptor ( β 2-AR), which plays a crucial role in facilitating bronchodilation ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…The CD79A (CD79a molecule) is encoded by the MB - 1 gene, and its mutation results in a complete arrest of B-cell development ( 24 ). F2R like trypsin receptor 1 (F2RL1) is a G-protein-coupled receptor ( 25 ) that is significantly upregulated in ovarian, cervical, and lung cancers, and enhances tumor cell proliferation, migration, and invasion ( 26 - 29 ). Glia maturation factor gamma (GMFG) is a 17 kDa protein, which mediates monocyte, neutrophil, and T-lymphocyte migration ( 30 - 32 ).…”
Section: Discussionmentioning
confidence: 99%